Quality of health information on websites with the greatest potential to influence users in the Czech Republic - Rusová, Jitka; Pleskot, Ondřej (Journal of Education Culture and Society, 2020)
Aim. To determine which websites most influenced Internet users in the Czech Republic in health matters, to assess the quality of these websites according to predetermined criteria, and to analyse the impact of the project MedLike. Methods. The points assigned to individual websites displayed when searching 734 terms (diseases and symptoms) were summed up to obtain a list of the most viewed websites. The quality of the websites was assessed according to predetermined criteria. Results. The websites with the greatest potential to influence Internet users in terms of health information (the most viewed websites) are ulekare.cz, mojezdravi.cz, cs.wikipedia.org. Most of them lack links to resources, information about the authors and dates of publication/updates. The articles are not easy to understand and contain unexplained medical terms. A vast majority of websites lacked updated information. Conclusion. Incorrect, misleading, and not up to date information was found in the articles. This can lead to the harm to the user.